1996
DOI: 10.1038/nsb1296-1040
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and NMR structure of Bet v 1, the origin of birch pollen allergy

Abstract: The three-dimensional structure of the major birch pollen allergen, the 17,500 M(r) acidic protein Bet v 1 (from the birch, Betula verrucosa), is presented as determined both in the crystalline state by X-ray diffraction and in solution by nuclear magnetic resonance (NMR) spectroscopy. This is the first experimentally determined structure of a clinically important inhalant major allergen, estimated to cause allergy in 5-10 million individuals worldwide. The structure shows three regions on the molecular surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
338
3
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(356 citation statements)
references
References 28 publications
13
338
3
2
Order By: Relevance
“…Previously, we showed that the tertiary structure of Pru av 1 (formerly Pru a 1) [3] from cherry (Prunus avium) in solution, determined by heteronuclear multidimensional NMR spectroscopy, is virtually identical with that of the major birch (Betula verrucosa) allergen Bet v 1 [4,5]. The main feature of the 3D (three-dimensional) structure is a folded seven-stranded antiparallel β-sheet and two short α-helices that wrap around a long C-terminal α-helix to form a basket-like structure with a large hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that the tertiary structure of Pru av 1 (formerly Pru a 1) [3] from cherry (Prunus avium) in solution, determined by heteronuclear multidimensional NMR spectroscopy, is virtually identical with that of the major birch (Betula verrucosa) allergen Bet v 1 [4,5]. The main feature of the 3D (three-dimensional) structure is a folded seven-stranded antiparallel β-sheet and two short α-helices that wrap around a long C-terminal α-helix to form a basket-like structure with a large hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…NMR spectroscopy, together with molecular modelling, fluorescence spectroscopy, X-ray crystallography and MS, provided strong evidence that the cavity of both Pru av 1 and Bet v 1 interacts with steroids and other lipids [7][8][9], but their exact physiological function remains unclear. The P-loop is one of three highly conserved regions on the surface of the Bet v 1 molecule proposed as IgE epitopes leading to cross-reactivity with pollen allergens of other trees of the Fagales order [5]. In the crystal structure of Bet v 1 in complex with a Fab fragment of the monoclonal murine IgG1 BV16, which was raised against Bet v 1 and partially inhibits binding of human IgE, the P-loop region constitutes the contact surface, with the side chain of Glu 45 located in a positively charged binding pocket forming two hydrogen bonds with the CDR3 (complementary determining region 3) of the heavy-chain variable domain [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is revealed by the structures of a number of PR-10 proteins obtained by NMR and x-ray crystallography, such as Bet v 1 from birch (Betula spp. ; Gajhede et al, 1996;Markovic-Housley et al, 2003), four isoforms of LlPR10 from yellow lupin (Lupinus luteus; Biesiadka et al, 2002;Pasternak et al, 2005;Fernandes et al, 2008), VrCSBP (cytokininspecific binding protein) from mung bean (Vigna radiata; Pasternak et al, 2006), Pru av 1 from cherry (Prunus avium; Neudecker et al, 2001), and Ap g 1 from celery (Apium graveolens; Schirmer et al, 2005).…”
mentioning
confidence: 99%
“…When analyzed by circular dichroism spectroscopy, the bacterially expressed rBet v 1 wild-type molecule was folded and consisted of mixed ␣ helical and ␤-sheet conformation (25,26). The three-dimensional structure of rBet v 1 was determined by x-ray crystallography and nuclear magnetic resonance analysis (27).…”
mentioning
confidence: 99%